The night detectives - Talton, Jon (Talton, Jon. David Mapstone mystery., 2013)
The private-detective business starts out badly for former Phoenix Deputy David Mapstone and his old friend Sheriff Mike Peralta. Mapstone and Peralta are hired to investigate the suspicious death of a young Arizona woman who fell from a condo tower in San Diego. The police call Grace Hunter's death a suicide, but the client, who is shot after hiring them and is found with multiple driver's licenses, doesn't agree. In San Diego, Mapstone finds Grace's boyfriend, who is trying to care for their baby. He, too, hires the pair to solve Grace's death. Their work reveals that this was no suicide, and Grace proves to be only the first victim of a murderous spree that reaches into the world of high-priced call girls, their millionaire clients, the white supremacist movement and a high stakes kidnapping.